2020
DOI: 10.1002/adsc.201901363
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Asymmetric Cross‐Dehydrogenative Coupling Reaction: Liquid‐Assisted Grinding Enables Reaction Acceleration and Enantioselectivity Control

Abstract: We report here a mechanochemical protocol for asymmetric cross‐dehydrogenative coupling (CDC) reaction of unreactive 3‐arylmethyl indoles with 1,3‐dicarbonyl by liquid‐assisted grinding. Small drops of liquid additive n‐butyl acetate (n‐BuOAc) are key to achieve high yield and enantioselectivity in this transformation. The catalyst can be lowered to 5 mol% and reused for three times. Pharmaceutical useful chiral dihydrocoumarins are further achieved through one‐pot tandem asymmetric CDC and cyclization with ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 96 publications
0
15
0
1
Order By: Relevance
“…However, most above mentioned approaches have reliance on toxic solvent, low temperature and/or inert atmosphere which are critical to the success of enantiocontrol. As the continuous study of LAG accelerated indole functionalization, Su's group recently reported a mechanochemical asymmetric cross‐dehydrogenative coupling reaction for the synthesis of chiral indoles (Scheme 15b) [99] . Essential to the success was the addition of catalytic amount of n ‐BuOAc enabling the dual‐control of reactivity and enantioselectivity.…”
Section: Pharmaceutical Fragments Construction and Functionalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most above mentioned approaches have reliance on toxic solvent, low temperature and/or inert atmosphere which are critical to the success of enantiocontrol. As the continuous study of LAG accelerated indole functionalization, Su's group recently reported a mechanochemical asymmetric cross‐dehydrogenative coupling reaction for the synthesis of chiral indoles (Scheme 15b) [99] . Essential to the success was the addition of catalytic amount of n ‐BuOAc enabling the dual‐control of reactivity and enantioselectivity.…”
Section: Pharmaceutical Fragments Construction and Functionalizationmentioning
confidence: 99%
“…Su's group recently reported a mechanochemical asymmetric cross-dehydrogenative coupling reaction for the synthesis of chiral indoles (Scheme 15b). [99] Essential to the success was the addition of catalytic amount of n-BuOAc enabling the dual-control of reactivity and enantioselectivity.…”
Section: Indole Derivativesmentioning
confidence: 99%
“…Strong covalent bonds, such as carbon-carbon and carbon-heteroatom (C-N, C-O, C-halogen, C-S, C-Se, and C-Te), can be activated by solid-state grinding under mild conditions of temperature and reagents. Examples of organic covalent reactions performed by mechanochemistry include dehydrogenative coupling, oxidation, reduction, and organocatalytic reactions [ 9 , 10 , 11 , 12 , 13 , 14 ]. Mechanochemistry has also been showing promising advances in organometallic synthesis [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Concordantly, many recent reports have described efforts to develop new strategies and catalysts to synthesize heteroaryl-bearing stereocenters with absolute stereocontrol. To cite limited examples, transition metal-mediated couplings [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], Petasis-like reactions [ 27 , 28 , 29 ], C—H functionalizations [ 30 , 31 , 32 , 33 , 34 , 35 ], Friedel–Crafts reactions [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ,…”
Section: Introductionmentioning
confidence: 99%
“…When heteroaryl trifluoroborate salts are used as nucleophiles, bis-heteroaryl stereocenters Concordantly, many recent reports have described efforts to develop new strategies and catalysts to synthesize heteroaryl-bearing stereocenters with absolute stereocontrol. To cite limited examples, transition metal-mediated couplings [17][18][19][20][21][22][23][24][25][26], Petasis-like reactions [27][28][29], C-H functionalizations [30][31][32][33][34][35], Friedel-Crafts reactions , and conjugate additions have provided significant advances . We have contributed to this area by demonstrating that α-chiral heterocycles can be synthesized through 3,3′-(bisperfluoroaryl)-BINOL (6)-catalyzed conjugate addition of aryl, alkenyl, and alkynyl boronic acids and trifluoroborate salts to β-heteroaryl-appended enones and enals [87][88][89][90].…”
Section: Introductionmentioning
confidence: 99%